Kebijakan Pertahanan Jepang Terhadap Keterlibatan Self Defense Force (SDF) Dalam United Nations Peacekeeping Operations (UN-PKO) (Studi Kasus: PKO di Sudan Selatan Tahun 2011-2017) - Hery Irawan; Khairur Rizki; Zulkarnain Zulkarnain (The Department of International Relations Universitas Mataram, 2021)
ABSTRACT This study aims to analyze how the development of Japan's defense policy affects the involvement of the Self Defense Force (SDF) in the United Nations Peacekeeping Operations (UN-PKO) especially in South Sudan in 2011-2017. This paper uses qualitative descriptive research model with secondary data. The data collection technique used is the study of literature by taking various reading sources such as books, journals, articles, official government portals as well as international news portals. Data analysis using Miles and Huberman models, namely the data collection stage, the data reduction stage, the data presentation stage, and the conclusion drawing stage. The results of this study show that the development of Japan's defense policy is influenced by Japan's response to international environmental conditions, strategy, defense doctrine, defense policy making process, changing military civil relations patterns, and relations with China and North Korea in the form of enmity. This further impacted the expansion of the role and responsibility of the Japanese SDF in peacekeeping operations, particularly PKO in South Sudan in 2011-2017. Keywords: Defense Policy, Self Defense Force, Peace Operations (PKO), Civil-Military Relations, South Sudan.